An Easily Constructed and Inexpensive Tool to Evaluate the Seebeck Coefficient - Rafiq Mulla (IEEE Transactions on Instrumentation and Measurement, 2021)
Genuinely inexpensive and easily constructable setup designs are important and encouraging for the new starters/students to build and use them as material testing tools during the initial stage of their research. A low-cost do it yourself (DIY) apparatus is designed and built for the accurate and reliable measurement of the Seebeck coefficient. The tool is portable and very easy to operate. It contains a miniaturized electrode designed for hot probe that helps data acquisition in a short time and avoids extra heat consumption and losses that occur in case of bulk probes. The tool also provides an easy sample loading/unloading facility; samples can be loaded/unloaded in just few seconds. It has been checked for its reliable working by measuring the Seebeck coefficient of some standard samples, giving reproducible measured data that are comparable to the literature values. The tool is suitable for the room temperature measurement but it is also demonstrated for temperature-dependent measurements up to 120 °C. As compared to most of the reported setups, the present design is simpler and can be built with commonly available raw materials. The tool is proposed as a simple, low-cost DIY testing unit for the thermoelectric materials.